The Royal Philanthropic Expedition Vaccine Against Smallpox and the Role of the Clergy in the Diocese of Chiapas (1803-1821) - Pérez Mendoza, Joel (Revista de historia., 2022)
In 1803, by order of King Carlos IV of Spain, an expedition was arranged to bring the smallpox vaccine to their territories in America. This expedition was in charge of the doctor Francisco Xavier Balmis, who arrived in New Spain in 1804 and later set sail for the Philippines. Secondary missions were sent to Tabasco, Oaxaca, Guatemala and Chiapas. The following pages analyze the way in which the sub-expedition that arrived at the intendencia de Ciudad Real de Chiapa was organized, paying special attention to the role played by the clergy in its application, as well as the difficulties it faced.